Nematode eel parasite found inside acanthocephalan cysts – a “Trojan horse” strategy? - Emde, Sebastian (Parasit Vectors, 2014)
BACKGROUND: The invasive eel parasite Anguillicoloides crassus (syn. Anguillicola crassus) is considered one of the major causes for the decline of the European eel (Anguilla anguilla) panmictic population. It impairs the swim bladder function and reduces swimming performance of its host. The life cycle of this parasite involves different intermediate and paratenic hosts. Despite an efficient immune system of the paratenic fish hosts acting against infections with A. crassus, levels of parasitized eels remain high in European river systems. Recently, the round goby Neogobius melanostomus (Gobiidae) has become dominant in many rivers in Europe and is still spreading at a rapid pace. This highly invasive species might potentially act as an important, so far neglected paratenic fish host for A. crassus. METHODS: Based on own observations and earlier single sightings of A. crassus in N. melanostomus, 60 fresh individuals of N. melanostomus were caught in the Rhine River and examined to assess the infection levels with metazoan parasites, especially A. crassus. Glycerin preparations were used for parasite identification. RESULTS: The parasite most frequently found in N. melanostomus was the acanthocephalan Pomphorhynchus sp. (subadult stage) which occurred mainly encysted in the mesenteries and liver. Every third gobiid (P = 31.7%) was infected by A. crassus larvae (L3) which exclusively occurred inside the acanthocephalan cysts. No intact or degenerated larvae of A. crassus were detected elsewhere in the goby, neither in the body cavity and mesenteries nor in other organs. Affected cysts contained the acanthocephalan larvae and 1–12 (mI =3) living A. crassus larvae. Additionally, encysted larvae of the nematode Raphidascaris acus were detected in the gobies, but only in the body cavity and not inside the acanthocephalan cysts. CONCLUSIONS: Based on our observations, we suggest that A. crassus might actively bypass the immune response of N. melanostomus by invading the cysts of acanthocephalan parasites of the genus Pomphorhynchus using them as “Trojan horses”. Providing that eels prey on the highly abundant round goby and that the latter transfers viable infective larvae of A. crassus, the new paratenic host might have a strong impact on the epidemiology of A. crassus.